Numerical homogenization of piezoelectric textiles with electrospun fibers for energy harvesting (Fracture and Structural Integrity, 2014)
Piezoelectric effects are exploited in an increasing number of micro- and nano-electro-mechanical systems. In particular, energy harvesting devices convert ambient energy (i.e. mechanical pressure) into electrical energy and their study is nowadays a very important and challenging field of research. In this paper, the attention is focused on piezoelectric textiles. Due to the importance of computational modeling to understand the influence that micro-scale geometry and constitutive variables have on the macroscopic behavior, a homogenization strategy is developed. The macroscopic structure behaviour is obtained defining a reference volume element (RVE) at the micro-scale. The geometry of the RVE is based on the microstructural properties of the material under consideration and consists in piezoelectric polymeric nano-fibers subjected to electromechanical contact constraints. This paper outlines theory and numerical implementation issues for the homogenization procedure. Moreover, within this approach the average response resulting from the analysis of different fiber configurations at the microscale is determined providing a multiphysics constitutive model for the macro-scale.
Keywords: Electromechanical Coupling